Indexing biographies and other stories of human lives - BELL, HAZEL K. (LIVERPOOL UNIV Press, 2020)
Stories of human lives can be fascinating but frequently difficult to index well. The new, updated fourth edition of Hazel K. Bell's Indexing Biographies is a valuable guide to the points for consideration when indexing life histories, biographies, autobiographies, letters and other narrative texts. Topics include the indexing of fiction, analysis of the text before indexing, names and their various forms, appropriate language choice for index entries, impartiality of the indexer, and how to treat main characters (through appropriate subheading structure) and minor characters (where strings of locators are sometimes unavoidable). The book also discusses more technical matters of index layout, presentation and arrangement of entries, such as how to judge whether alphabetical, chronological, page order or thematic grouping is most appropriate for the text. Examples of good practice and outstanding indexes are provided throughout. Lists of useful reference works and relevant articles f...